Risk factors and new inflammatory indicators of deep vein thrombosis after adult patella fractures - Diao, Shuo; Li, Jingqiao; Zhao, Jianyong; Wang, Dong; Wang, Hanzhou; Xu, Xiaopei; Zhou, Junlin (Frontiers in Surgery, 2022)
Background: This study aimed to investigate the association between new inflammatory indicators at admission and the occurrence of preoperative deep vein thrombosis (DVT) in patients with patella fractures. Methods: A retrospective analysis of the medical records of patients aged 18 years or older who underwent surgical treatment for unilateral closed patella fractures at our hospital between August 2016 and August 2020. The incidence of preoperative DVT was detected by Duplex ultrasound (DUS). Partial blood routine and biochemical indexes were collected at admission, and the neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), and platelet-to-lymphocyte ratio (PLR) of inflammatory indexes were also calculated. ROC was used to analyze the cut-off value NLR, MLR, and PLR for predicting preoperative DVT, and univariate and multivariate analyses of the risk factors for preoperative DVT of patella fractures, and to verify whether other risk factors affecting the relationship between validation indexes and preoperative DVT. Results: A total of 500 patients were included, of which 39 patients (7.8%) developed preoperative DVT. After univariate and multivariate analysis, preoperative time (in each day delay), male (vs. female), D-dimer > 0.6 mg/L, TC > 5.6 mmol/L, and PLR > 189.8 were the risk factors for preoperative DVT in patients with patella fracture. Inflammation index PLR combined with the other four risk factors significantly improved the predictive efficacy of preoperative DVT compared with PLR (P = 0.009). Conclusion: Inflammatory index PLR is a risk factor for preoperative DVT in patients with patella fracture, and the efficacy of PLR in predicting DVT can be significantly improved when other risk factors (male, D-dimer > 0.6 mg/L, TC > 5.6 mmol/L, and PLR > 189.8 ) are combined. These data are useful for the clinical identification of patients at high risk of DVT before patella fracture.